Enhancing Care and Advocacy for Sexual Assault Survivors on Canadian Campuses - Quinlan, Elizabeth; Clarke, Alison; Miller, Natasha (Canadian Journal of Higher Education, 2016)
Recent media coverage of the rape chant at Saint Mary’s University, the misogynist Facebook posts at Dalhousie’s dental school, and the suspension of the University of Ottawa’s hockey team have brought the topic of campus sexual assault under intense public scrutiny and the media accounts point to a widespread systemic rape culture on Canadian campuses. The objective of this paper is to examine the existing structure of campus sexual assault services at Canadian universities and colleges in order to highlight best practices and barriers to their success. The study’s data collection entailed an environmental scan of existing programs and campus-community collaborations across Canada, and a half-day symposium in which stakeholders reviewed the scan’s results and developed recommendations. The study’s findings indicate that most campus sexual assault and women’s centres rely on volunteers and collaboration with off-campus organizations in order to maintain a breadth of services for sexual assault survivors. Funding challenges were found to impose significant limitations to the functionality of the centres. The paper closes with recommendations for improvements, including public education programming and dedicated services provided by professionals with specialized training and experience.